Harrell V. Noble papers - Noble, Harrell V. (Harrell Vaun), 1907-1982.
Correspondence, speeches, writings, biographical material, printed matter, awards, artifacts, photographs, and other papers relating primarily to Noble's career in electronic engineering. Documents his work involving radios and transmitters especially during World War II and molecular electronics, today called microelectronics, at the Westinghouse Electric & Manufacturing Company and at Wright-Patterson Air Force Base. Includes material pertaining to his years at the Radio Corporation of America and the Crosley Radio Corporation relating to the development of commercial and government transmitters and World War II radio receivers, transmitters, and radars. Correspondents include Noble's daughter, Linda C. Joseph, William C. Brown, Stewart Cummins, Amos H. Dicke, Jack St. Clair Kilby, and G. Ross Kilgore.
Engineer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown, William C., -- 1916- -- Correspondence; Cummins, Stewart -- Correspondence; Dicke, Amos H. -- Correspondence; Joseph, Linda C. -- Correspondence; Kilby, Jack S. -- 1923-2005 -- Correspondence; Kilgore, G. Ross -- Correspondence; Crosley Radio Corporation; Radio Corporation of America; Westinghouse Electric & Manufacturing Company; Electrical engineering; Electronics; Microelectronics; Molecular electronics; Radar; Radio; Radio -- Receivers and reception; Radio -- Transmitters and transmission; World War, 1939-1945.; Wright-Patterson Air Force Base (Ohio); Engineers